Pendugaan sebaran intrusi air laut melalui sungai di desa Ujungmanik kecamatan Kawunganten kabupaten Cilacap menggunakan metode geolistrik resistivitas konfigurasi Wenner - Muhammad Sehah; Mitha Syahfitri; Sunardi Sunardi (Jurnal Teras Fisika: Teori, Modeling, dan Aplikasi Fisika, 2021)
The estimation of the distribution of the sea water intrusion through the rivers in Ujungmanik Village, Kawunganten District, Cilacap Regency has been carried out using the Wenner configuration resistivity geoelectric. This research aims to estimate the distribution of sea water intrusion through rivers in Ujungmanik Village, Kawunganten District, Cilacap Regency based on geoelectric resistivity and conductivity data of groundwater. The geoelectric data acquisition was carried out on four lines. They were Wen1 Line, Wen2 Line, Wen3 Line, and Wen4 Line. Each line had a range of 200 meters. The results of geoelectric data processing showed that the subsurface rock structure consisted of sand, clay, sandy loam, and sandy clay. The Seawater intrusion shown by the sand layer occurred in all trajectories which had a range of resistivity value of 0.20 - 2.79 Ωm. Groundwater samples was carried out at fifteen points with the conductivity value varies between 1363 - 4145 µS / cm so that they can be classified that the water was fresh and brackish due to the sampling done in the rainy season. From this research it can be implied that the entire Ujungmanik area is evenly intruded by the sea water at the coordinates 7º38ꞌ15.62ꞌꞌLS 108°57ꞌ20.89ꞌꞌBT to 7º39ꞌ22.86ꞌꞌLS 108º56ꞌ35.33ꞌꞌBT.